Emergence of Orai3 activity during cardiac hypertrophy. (11th September 2014) - Saliba, Youakim; Keck, Mathilde; Marchand, Alexandre; Atassi, Fabrice; Ouillé, Aude; Cazorla, Olivier; Trebak, Mohamed; Pavoine, Catherine; Lacampagne, Alain; Hulot, Jean-Sébastien; Farès, Nassim; Fauconnier, Jérémy; et al.
Abstract: Aims: Stromal interaction molecule 1 (STIM1) has been shown to control a calcium (Ca 2+ ) influx pathway that emerges during the hypertrophic remodelling of cardiomyocytes. Our aim was to determine the interaction of Orai1 and Orai3 with STIM1 and their role in the constitutive store-independent and the store-operated, STIM1-dependent, Ca 2+ influx in cardiomyocytes. Methods and results: We characterized the expression profile of Orai proteins and their interaction with STIM1 in both normal and hypertrophied adult rat ventricular cardiomyocytes. Orai1 and 3 protein levels were unaltered during the hypertrophic process and both proteins co-immunoprecipitated with STIM1. The level of STIM1 and Orai1 were significantly greater in the macromolecular complex precipitated by the Orai3 antibody in hypertrophied cardiomyocytes. We then used a non-viral method to deliver Cy3-tagged siRNAs in vivo to adult ventricular cardiomyocytes and silence Orai channel candidates. Cardiomyocytes were subsequently isolated then the voltage-independent, i.e. store-independent and store-operated Ca 2+ entries were measured on Fura-2 AM loaded Cy3-labelled and control isolated cardiomyocytes. The whole cell patch-clamp technique was used to measure Orai-mediated currents. Specific Orai1 and Orai3 knockdown established Orai3, but not Orai1, as the critical partner of STIM1 carrying these voltage-independent Ca 2+ entries in the adult hypertrophied cardiomyocytes. Orai3 also drove an arachidonic acid-activated inward current. Conclusion: Cardiac Orai3 is the essential partner of STIM1 and drives voltage-independent Ca 2+ entries in adult cardiomyocytes. Arachidonic acid-activated currents, which are supported by Orai3, are present in adult cardiomyocytes and increased during hypertrophy.